2019
DOI: 10.1080/13880209.2019.1687525
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of Cinnamomum hydroethanolic extract improves wound healing by enhancing re-epithelialization and keratin biosynthesis in streptozotocin-induced diabetic mice

Abstract: Context: Cinnamomum verum J. Presl. (Lauraceae) has a high number of polyphenols with insulin-like activity, increases glucose utilization in animal muscle, and might be beneficial for diabetic patients. Objective: This study evaluated the effectiveness of an ointment prepared from Cinnamomum verum hydroethanolic extract on wound healing in diabetic mice. Materials and methods: A total of 54 male BALB/c mice were divided into three groups: (1) diabetic non-treated group mice that were treated with soft yellow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“… 2016 ; Daemi et al. 2019a ). The results showed that the topical application of ZMEO increased fibroblast, which is due to its effect on IGF-1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 2016 ; Daemi et al. 2019a ). The results showed that the topical application of ZMEO increased fibroblast, which is due to its effect on IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the TTM, the collected granulation tissue sample was homogenized and the supernatant was added to Tris-EDTA as reported by Daemi et al. ( 2019a ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations